ChemInform Abstract: Ba1.63La7.39Si11N23 Cl0.42:Ce3+ — A Nitridosilicate Chloride with a Zeolite‐Like Structure. Issue 29 (June 2016) - Schultz, Peter; Durach, Dajana; Schnick, Wolfgang; Oeckler, Oliver
Abstract: Red platelet‐shaped crystals of Ba1.63 La7.39 Si11 N23 Cl0.42 :Ce 3+ are selected from samples prepared by metathesis reaction of "Si2 (NH)3 ·6NH4 Cl" (the product of the ammonolysis of Si2 Cl6 ), LaCl3, BaH2, and CeF3 (W crucible, 1.